Lupus Anticoagulants and Thrombosis: Clinical Association of Different Coagulation and Immunologic Tests - Galli, Monica; Dlott, Jeffrey; Norbis, Francesca; Ruggeri, Luisa; Cler, Linda; Triplett, Douglas A.; Barbui, Tiziano (Thrombosis and Haemostasis, 2000)
The dilute Russell’s viper venom time (dRVVT) and the kaolin clotting time (KCT) are two among the most commonly used coagulation tests for the detection of lupus anticoagulants. The dRVVT seems superior to the KCT in identifying LA-positive patients at risk of thrombosis. However, this relationship is greatly influenced by both the source of reagents and the instrumentation employed to carry out the assays. Therefore, 4 dRVVTs (“home-made” dRVVT, DVV test, Bioclot LA, LA Screen), and one KCT (Kaoclot) were performed in two centers and compared for their retrospective correlation with the thrombotic complications of 72 patients with a previously established diagnosis of lupus anticoagulants. Two other assays (“home-made” KCT, and Colloidal Silica Clotting Time, CSCT) were performed in one of the two centers, and compared with Kaoclot for their clinical correlations in the same population of patients, 44 of whom (61%) had suffered from arterial and/or venous thrombosis. A rather good degree of inter-laboratory and inter-assay correlations of the different tests was found. However, a statistically significant association with thrombosis was found only with the coagulation profile generated using the “homemade” dRVVT. When the commercially available dRVVTs were used, none of the coagulation profiles remained associated with thrombosis. When the assays were analyzed separately, the association with thrombosis was statistically significant for LA screen (p = 0.0019), DVV test (p = 0.0043), and Bioclot (p = 0.0255), and of borderline significance for the “home-made” dRVVT (p = 0.0503) in one center. This last assay was also significantly associated with thrombosis in the other center (p = 0.0139). When venous and arterial thrombosis were considered separately, DVV test was statistically associated with venous thrombosis in both centers (p = 0.0076 and p = 0.0187, respectively), and LA screen in one center (p = 0.0303). No dRVVT was found to correlate with arterial thrombosis. Kaoclot, Colloidal Silica Clotting Time, and the “home-made” KCT did not correlate with thrombosis. The prevalence of IgG and/or IgM antibodies to cardiolipin, β2-glycoprotein I and prothrombin were 74%, 86% and 85%, respectively. Increased titers of IgG anticardiolipin antibodies were associated with arterial thrombosis (p = 0.0375), whereas IgM anti-β2-glycoprotein I antibodies were associated with venous thrombosis (p = 0.0433). In conclusion, these retrospective data support the notion that the dRVVT, rather than other coagulation or ELISA tests, are able to identify lupus anticoagulant-positive patients at risk of thrombosis. This property appears common to several commercially available dRVVT kits, making this type of assay the ideal target of future efforts of laboratory standardization.
Keywords: Lupus anticoagulants; thrombosis; dRVVT; antiphospholipid antibodies